Pengaruh Kepemimpinan, Komunikasi, Dan Lingkungan Kerja Terhadap Semangat Kerja Karyawan (Studi Pada Karyawan PD. BPR BKK Wonogiri) - Sodik Prasojo, Ahmad; , Drs. M. Farid Wajdi, MM., Ph.D (2017)
The purpose of this study was to analyze the influence of leadership, communication and work environment on employee morale PD. BPR BKK Wonogiri partially or jointly. This type of research is quantitative, with a population of PD employees. BPR BKK Wonogiri as many as 50 employees, with a sample of 50 people. Sampling using saturation sampling or total sampling. Methods of data collection research using a questionnaire with Likert scale. Data were analyzed using analysis instrument test data, the classical assumption test, multiple linear regression. Based on the calculation of the t-test, F shows the variables of leadership, communication, and working environment together have a significant effect on morale. The coefficient of determination R2 obtained a yield of 0.768 means that the variables of leadership, communication and working environment able to explain the variation of the variable changes in employee morale by 76.8%, the rest can be explained other variables that are not included in the research model.